(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article reconstructs the political biography of Santos Degollado, an important figure in the liberal project carried out in Mexico by political leaders led by Benito Juárez. Since Degollado’s particular history coincides with the period of Mexico’s formation as a nation, his biography sheds light on key actors who influenced their historical context. This particular vantage point thus allows for greater comprehension of broad historical processes.